2002
DOI: 10.1053/jhep.2002.36129
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of an outbreak of acute hepatitis C among healthy volunteers participating in pharmacokinetics studies

Abstract: We identified 15 patients with acute hepatitis C (AHC) among 29 healthy volunteers participating in 2 consecutive pharmacokinetics studies. Molecular techniques were used to determine the relatedness of viral strains, whereas clinical and virologic follow-up was started to establish the course and outcome of the acute infection. After presentation, serum liver enzymes and HCV RNA were monitored weekly for 4 months, then monthly for at least 12 months. Liver biopsy was performed 6 to 12 months after AHC diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
40
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 41 publications
6
40
0
Order By: Relevance
“…Icteric patients tend to have a higher rate of spontaneous viral clearance than those with milder or asymptomatic course. In two recent studies, it was shown that acute symptomatic infection resolved in more than 50% of patients [13,14], whereas the overall recovery from primary HCV infection is believed not to exceed 15% [15]. Our study also confirmed a greater chance for recovery from HCV infection in those with higher aminotransferase activity, especially ALT.…”
Section: Discussionsupporting
confidence: 84%
“…Icteric patients tend to have a higher rate of spontaneous viral clearance than those with milder or asymptomatic course. In two recent studies, it was shown that acute symptomatic infection resolved in more than 50% of patients [13,14], whereas the overall recovery from primary HCV infection is believed not to exceed 15% [15]. Our study also confirmed a greater chance for recovery from HCV infection in those with higher aminotransferase activity, especially ALT.…”
Section: Discussionsupporting
confidence: 84%
“…Since up to 53% of patients with acute HC show a self-limiting course of the disease Hofer et al, 2003;Hoofnagle, 2002;Larghi et al, 2002), not all patients with acute HC may require treatment. Patients clearing the virus spontaneously can be identified by measuring viral load frequently during the first weeks of the disease (Hofer et al, 2003;Spada et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Acute infection is largely asymptomatic with persistent infection developing in 43-86% of the cases [2][3][4][5][6][7][8][9][10][11], and it is likely that the vast majority runs unrecognised for several years until major complications secondary to decompensated liver disease may eventually develop. Fulminant hepatic failure is a rare, if at all associated, complicating event.…”
mentioning
confidence: 99%